1992
DOI: 10.1016/0020-7292(92)90660-b
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and hormonal profile of Panamanian women during the menstrual cycle

Abstract: Forty-one women of reproductive age were included in the study, to establish the variation of serum lipids during the menstrual cycle and simultaneously, to determine the physiological fluctuation of FSH, LH, prolactin (PRL), progesterone (P4) and estradiol (E2) concentration in serum, during the menstrual cycle. A significant decrease of total serum cholesterol (165.29 +/- 3.6 mg/dl) and triglycerides (108.99 +/- 9.65) occurred during the luteal phase, as compared with the follicular phase (176.16 +/- 3.51, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Our finding of a decline in total cholesterol and LDL-C over the course of the menstrual cycle is consistent with previous studies by Kim and Kalkhoff, 25 who reported values for both parameters, and Jones et al, 26 Lussier-Cacan et al, 27 Tangney et al, 28 and De Leon et al, 29 who reported only total cholesterol concentrations. Lebech and Kjoer, 30 Woods et al, 31 and Karpanou et al 32 did not, however, observe changes in total and LDL-C during the menstrual cycle in healthy women.…”
Section: Discussionsupporting
confidence: 82%
“…Our finding of a decline in total cholesterol and LDL-C over the course of the menstrual cycle is consistent with previous studies by Kim and Kalkhoff, 25 who reported values for both parameters, and Jones et al, 26 Lussier-Cacan et al, 27 Tangney et al, 28 and De Leon et al, 29 who reported only total cholesterol concentrations. Lebech and Kjoer, 30 Woods et al, 31 and Karpanou et al 32 did not, however, observe changes in total and LDL-C during the menstrual cycle in healthy women.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies report no significant differences in plasma TG concentration at various time points during a menstrual cycle (8,32,33), whereas in other studies plasma TG concentration was found to be lower during the luteal phase (LP) than during the follicular phase (FP) (13,42). Some of the discrepancy between findings from different studies may be due to differences in timing within each cycle phase; both plasma estradiol and progesterone concentrations vary markedly within the FP and LP.…”
mentioning
confidence: 97%
“…Levels of FSH, LH, E2, and P4 are dramatically different at the different phases of the menstrual cycle, which causes greater variation than diurnal variation. 35,36 Prolactin levels are little affected by the menstrual cycle, but are affected by the time of day, relatively high in the evening, relatively low during the day, and close to average in the morning. 37 Serum testosterone level is the highest at around 11:00 AM and the lowest at midnight at around 2:00 AM.…”
Section: Discussionmentioning
confidence: 97%